Modeling Of Mechanical Properties of Ceramic-Metal Composites for Armor Applications - Mansur, Ali (Université d'Ottawa / University of Ottawa, 2011)
In this study, AISI 450 stainless steel and ceramic-metal matrix composites (CMMCs) impacted by a 7.61x51mm armor piercing (AP) projectile, are numerically investigated by using Abaqus/Explicit. For AISI steel, three different failure criteria are used in order to determine the critical thickness values for perforation for different projectile impact velocities. Overall, the standard Abaqus and the elongation to fracture criteria yield comparable results, while the strain energy model yields critical plate thickness values nearly twice as large as those obtained using the two other models. Because of the unavailability of most parameters needed for the standard ductile-shear criteria, only the alternative failure criteria, elongation to fracture and strain energy, were used for CMMCs, specifically WC-CO. This result is contrary to the real condition experience and expectation that CMMCs provide better ballistic performance. It can be rationalized by the non-consideration of local heating and shear band formation in this study.